2018
DOI: 10.1093/annweh/wxy021
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Ageing at Work in Chile: Employment, Working Conditions, Work–Life Balance and Health of Men and Women in an Ageing Workforce

Abstract: Results indicate that Chileans working into old age face precarious jobs with limited protection and several adverse working conditions. Noteworthy, women carry the double burden of paid and unpaid work into their late years. In addition, results suggest they are affected more profoundly by the healthy worker effect whereby the health condition determines the probability of finding and keeping a job-also known as a health selection mechanism-which increases as they age. These employment and working conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 8 publications
2
24
0
6
Order By: Relevance
“…De esta forma, para ellas, la vejez no necesariamente es un tiempo de descanso, en comparación de lo que podría ser para las profesionales. Esto condice con estudios que muestran que un importante número de mujeres sigue trabajando posterior a la edad de jubilación, principalmente por necesidad económica (CEVE-UC, 2018), sobrellevando la carga del trabajo remunerado y no remunerado en su vejez(Vives, Gray, González, & Molina, 2018).Finalmente, los resultados de esta investigación aluden a una paradoja aparente: si bien hay heterogeneidad en la vejez, esta también nos une. Los imaginarios sociales e individuales de vejez son compartidos, a pesar de la diversidad etaria y ocupacional, y de la heterogeneidad en el proceso de envejecer y en la vejez.…”
unclassified
“…De esta forma, para ellas, la vejez no necesariamente es un tiempo de descanso, en comparación de lo que podría ser para las profesionales. Esto condice con estudios que muestran que un importante número de mujeres sigue trabajando posterior a la edad de jubilación, principalmente por necesidad económica (CEVE-UC, 2018), sobrellevando la carga del trabajo remunerado y no remunerado en su vejez(Vives, Gray, González, & Molina, 2018).Finalmente, los resultados de esta investigación aluden a una paradoja aparente: si bien hay heterogeneidad en la vejez, esta también nos une. Los imaginarios sociales e individuales de vejez son compartidos, a pesar de la diversidad etaria y ocupacional, y de la heterogeneidad en el proceso de envejecer y en la vejez.…”
unclassified
“…Gender gaps in employment have been attributed to women having to care for the socially weak population, including childbearing and childrearing. Meanwhile, the employment status of men is less affected, owing to the influence of labor market productivity on the probability of men’s labor force [ 12 , 26 ]. Indeed, studies have consistently indicated that women were more involved in family roles and had higher expectations of those roles than men [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gendered inequalities vary with respect to employment and working conditions, with differences seen in occupations and economic activities, contract types, wages, access to labor rights and benefits, and working times [ 11 , 12 ] which can have beneficial or damaging effects on health. As indicated by the WHO, the unequal distribution of working conditions is a key contributor to social inequalities in health.…”
Section: Introductionmentioning
confidence: 99%
“…It is characteristic that older workers are in better health than nonworkers. And such an observation is characteristic of the female sex to a greater extent [4].…”
Section: Introductionmentioning
confidence: 96%
“…Consideration should also be given to the effect of age on the level of discrimination in both sexes. High labor intensity and requirements for physical indicators in men, as well as comparatively lower pay among women, are risk factors for stress at work in persons of pre-retirement age [4]. It is characteristic that older workers are in better health than nonworkers.…”
Section: Introductionmentioning
confidence: 99%